RAPID ASSIMILATION OF THE DECISION TREE LEARNING ALGORITHM - Sultangaliev Amirkhan Manasovich (Galaxy International Interdisciplinary Research Journal, 2022)
We know that it will take a very long time to learn for a decision tree, and to solve this problem, we offer several ways of learning that will not take much time.